Taxing informality: Compliance and preferences in urban Zambia - Resnick, Danielle (Taylor and Francis, 2021)
What drives tax compliance among informal workers, and how does compliance affect their preferences? Informal workers in developing countries encounter multiple taxes levied by government authorities and non-state actors. Using an original survey of approximately 800 informal workers in Lusaka, Zambia, this paper shows that compliance is tied to the governance setting where workers operate. In cooperative markets, compliance is higher where services are better and where trust in market leaders is stronger. Yet, in markets overseen by the city council, revenue collection capacity is more relevant. This suggests that the drivers of compliance can vary depending on the routes of accountability between tax payers, revenue collectors, and service providers. A vote choice experiment further reveals that regardless of market type, those who pay taxes are more likely to favour a politician interested in improving market services rather than one campaigning to improve the city’s schools and health clinics. The results suggest that even within the informal sector, the process of paying taxes affects preferences and shapes citizens’ preferences for elected leaders who espouse a platform most congruent with their own priorities.